Analysis of The Use of AI in Detecting Managerial Fraud: Systematic Literature Review - Nadila, Nadila; Panggeso, Anastasia Gloria; Usman, Asri; Mediaty, Mediaty (Program Studi Akuntansi FPEB UPI, 2024)
This article discusses the role of artificial intelligence (AI) in managerial fraud detection, a critical issue for many organizations. In recent years, technology has driven the use of AI to identify and prevent fraud, such as misleading financial statements and asset misappropriation. AI offers a more sophisticated approach than traditional techniques, using big data analytics and machine learning algorithms to detect suspicious patterns with high accuracy. By leveraging historical and real-time data, AI systems can spot anomalies that humans might miss. The application of this technology increases the efficiency of fraud detection and helps organizations take more proactive preventive measures, potentially reducing the cost of investigations and litigation. However, challenges such as ethical issues, data privacy, and algorithm transparency need to be addressed. Overall, the potential for AI to improve integrity and accountability in management is significant, making it a critical tool in maintaining organizational health. With the ever-increasing complexity of the business environment, the use of AI in managerial fraud detection is expected to continue to grow.